Efektivitas Program MBG (Makan Bergizi Gratis) dalam Meningkatkan Kesejahteraan Masyarakat Penerima Sasaran dalam Perspektif Maqashid Syariah - Syauqi Alaika Rahman; Hayatul Millah; Lailatul Azizah (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The Free Nutritious Meal Program (MBG) is a government initiative aimed at improving community welfare by fulfilling the nutritional needs of vulnerable groups, including school-age children, toddlers, and pregnant women. Beyond functioning as social assistance, the program seeks to enhance the quality of human resources, reduce economic vulnerability, and promote healthier and more productive communities. This study aims to analyze the effectiveness of the MBG Program in improving the welfare of beneficiaries from the perspective of Maqasid al-Shariah. A qualitative field research approach was employed at the Hafshawaty Nutrition Fulfillment Service Unit (SPPG) in Temenggungan Village, Krejengan District, Probolinggo Regency. Data were collected through observation, interviews, and documentation and analyzed using data reduction, data presentation, and conclusion-drawing techniques. The findings indicate that the MBG Program has been relatively effective in improving the welfare of beneficiaries by supporting nutritional fulfillment, enhancing health conditions, and contributing to social well-being. From the Maqasid al-Shariah perspective, the program aligns with the objectives of preserving life (hifz al-nafs) and promoting public benefit (maslahah). The study recommends strengthening program implementation through improved distribution supervision, better nutritional quality, and more accurate beneficiary targeting. Sustainable collaboration among the government, SPPG, and the community is essential to maximize program effectiveness and ensure long-term welfare improvements.